THE ROLE OF DATA SUPERVISORS IN THE IMPLEMENTATION OF PRIVACY POLICIES: A LITERATURE REVIEW - Loso Judijanto; Al-Amin (ADISAM PUBLISHER, 2025)
In the ever-evolving digital age, the protection of personal data is becoming increasingly crucial. This study reviews the existing literature on the role of data supervisors in the implementation of privacy policies in various organisations. Data supervisors play an important role in ensuring that the collection, storage and use of personal data comply with applicable privacy regulations. The results of the study show that although this role is essential, data supervisors face various challenges including rapid regulatory changes, technological advances, and the need to manage data efficiently. Technological literacy and continuous training are key to overcoming these challenges. In addition, collaboration between data supervisors and other internal stakeholders is needed to ensure that privacy policies are implemented effectively and are responsive to changes in the digital environment. Therefore, this study emphasises the importance of the strategic role of data supervisors in creating a data management system that complies with the law and is oriented towards individual privacy rights.